Designing New Financial Instruments to Work in the Asian Markets - Viktorovich Akinin, Peter; Petrovna Akinina, Valentina; Olegovna Alimova, Inna; Olegovna Boldareva, Yuliya; Valeryevna Viderker, Natalya (International Journal of Engineering and Technology, 2018)
This article is the methodology for analyzing the design of new financial instruments associated with the ongoing revolutionary changes in the financial system, the development of financial engineering, which led to the spread of new products that had become available to a wide range of consumers.Let us select the following tasks:â€“ to determine the objective need to study the main characteristics of new modified innovative financial products (structured);â€“ to justify the need to create a completely new financial product determined by the dominant group of goods [typical of the financial markets of the Far East], taking into account their specificity and the change of orientation towards the Asian markets, by the increasing activity in the Eastern vector and by the ability to trade in the national currency;â€“ to propose and test the methodology for creating a structured financial instrument that meets modern geopolitical challenges, with the inclusion of the price calculated on the basis of the consensus forecast.Â Â